COMPARATIVE STUDY OF BUPIVACAINE WITH DEXMEDETOMIDINE VERSUS BUPIVACAINE WITH CLONIDINE FOR SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK FOR UPPER LIMB SURGERIES - KALLURI SAIPRIYANKA; NAGAJYOTHI J (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To compare the efficacy of clonidine with dexmedetomidine as an adjunct to bupivacaine in patients undergoing upper limb surgeries under supraclavicular brachial plexus block. Methods: This was a prospective comparative study conducted in the department of anesthesiology of a tertiary care medical institute. 80 patients undergoing various upper-limb surgeries were included in this study. Patients were divided into two groups on the basis of whether they received Clonidine (Group C) or Dexmedetomidine (Group D) as an adjuvant to Bupivacaine for supraclavicular block. The onset as well as duration of sensory and motor blockade, duration of analgesia, quality of anesthesia, hemodynamics, and adverse effects were compared between the two groups. p<0.05 was considered statistically significant. Results: The gender distribution of cases in Group C and Group D was found to be comparable, with no statistically significant difference. The mean age of patients in both groups was found to be comparable with no significant difference (p=0.5671). The most common types of surgeries in the studied cases were those of the lower radius and ulna (28.75%), followed by the lower humerus (21.25%), upper radius, and ulna (20%). The mean duration of sensory and motor block and duration of analgesia were found to be higher in group D as compared to group C, and the difference was found to be statistically highly significant (p<0.0001). The quality of anesthesia was better in patients who received dexmedetomidine as compared to those who received clonidine with Bupivacaine. Conclusion: Dexmedetomidine used as an adjuvant with bupivacaine for brachial plexus block is associated with prolonged duration of sensory as well as motor block and duration of analgesia as compared to when clonidine is used as an adjuvant. It is also associated with a better quality of anesthesia.